Antepartum Evaluation of the Fetus and Fetal Well Being - O'NEILL, ERICA (2012)
Despite widespread use of many methods of antenatal testing, limited evidence exists to demonstrate effectiveness at improving perinatal outcomes. An exception is the use of Doppler ultrasound in monitoring high-risk pregnancies thought to be at risk of placental insufficiency. Otherwise, obstetricians should proceed with caution and approach the initiation of a testing protocol by obtaining an informed consent. When confronted with an abnormal test, clinicians should evaluate with a second antenatal test and consider administering betamethasone, performing amniocentesis to assess lung maturity, and/or repeating testing to minimize the chance of iatrogenic prematurity in case of a healthy fetus.